Internet Addiction: An Exploratory Study on Malaysian Internet Users - Sinnappan, Sukunesan (1999)
Internet has become a part of our daily lives. The vast scale of internet moves the whole society and culture into an entirely new dimension. With the media giving so much attention to the internet, more and more people are getting involved but some seem to be a bit too involved. It is becoming common to know someone, or have heard of someone, that has become obsessed with on-line activities to the point that they ignore important personal responsibilities. However, despite the increasing importance of internet, little attention seem to have been paid towards understanding internet dependency or addiction. This study was conducted specifically to determine 1) the existence of internet addiction, 2) which demographic factor and personality type correlates with internet addiction, 3) the characteristics of internet users and as well as possible addicts.The study was conducted on active internet users, who get their access to internet via cybercafes in Klang Valley. A total of 136 individuals participated in the study. Data were collected through self-administered questionnaire and were analysed using statistical analyses such as frequency, percentage, correlation and Chi-square, by means of SPSS-Win computer software. The findings show that the internet users in cybercafes are young, educated, mostly males with low income. These young users also have strong peer influence and are willing to forgo their recreational activities and personal responsibilities in order to stay on-line. Being youths internet is mainly used for entertainment, research and communication purposes. Internet is sought after by these users due to the quantity of information and its excellent networking capabilities. Affordable charges at the cybercafes has facilitated these youths to continue their net habits there. Peer company and influence, easy access to the internet and appealing facilities are the main reasons of these young users visit cybercafes.In midst of getting exposed and familiarised with internet, some get obsessed. Internet addiction was found existing among Malaysian internet users. These addicts are aware of their extensive usage and intend to reduce. Based on the findings of this study, there is a need for recovery programs and therapy to cure these addicts. And various in depth studies should be carried out to cope with the social implications of this latest communication technological tool.